Profile of Children with Special Needs of the Slow Learner Variety SMP Madura - Ilzam, Ahmadur; Naqiyah , Najlatun; Habsy, Bakhrudin All (International Journal of Social Science and Religion (IJSSR), 2023)
Slow Learner is part of one of the children with special needs but still above disability. This study aims to determine the profile of slow-learning children commonly called slow learners in one of the junior high schools in Madura. This research uses a qualitative case study approach with data collection methods of observation, interviews, and documentation. The results of this study are that of students who experience slow learning, 60% are caused by hereditary and genetic factors and 40% are caused by environmental factors originating from families who use authoritarian family education. This affects the learning process of children who are of course intellectually all of them are below the average of other normal children when looking at the academic scores obtained so that the school takes an attitude of maximizing children's learning and cooperating with related parties.